Analysis of the utilization of landsat 8 oli imagery for mapping the distribution of coral reefs in Pulau Weh Sabang - M Taufik Rahmadi; Sugiharto Sugiharto; Mbina Pinem; Ayu Suciani (Depik, 2021)
As one of the largest archipelagic countries globally, Indonesia has diverse natural resources, one of which is the coral reef ecosystem. Coral reef ecosystems are spread across almost all Indonesian waters, and Pulau Weh Sabang is one distribution area. This study aims to determine the distribution of coral reef ecosystems and test landsat 8 oli imagery accuracy in mapping coral reef ecosystems. The method used in this research is the nearest neighbour algorithm object-based classification method. The results showed that the coral reef ecosystem in Pulau Weh Sabang was divided into two classes: a healthy coral reef ecosystem class with 277.38 hectares and a medium condition coral reef ecosystem class with an area of 710.01 Ha.Keywords:Landsat 8 oliMappingDistributionCoral reefWeh Island